Collective decision-making in the health non-governmental organisation (NGO) sector in South Africa - Mazunga, Peter (https://orcid.org/0000-0003-4968-6034) (Rhodes University, 2026)
This thesis investigates the dynamics of collective decision-making within the health non-governmental organisation (NGO) sector in South Africa. Although NGOs play an essential role in bridging gaps in healthcare service delivery, limited attention has been given to how strategic decisions are made within these organisations, particularly under conditions of funding volatility, donor dependency, regulatory compliance, and organisational complexity. To address this gap, the study employs a qualitative research design grounded in Strauss and Corbin's (1990) version of grounded theory, generating a contextually embedded understanding of collective decision-making in health NGOs. Empirical data were gathered through in-depth interviews with strategic leaders across five diverse health NGOs. The data was analysed using open, axial, and selective coding to develop categories, relationships, and conceptual linkages. The findings reveal three typologies of strategic collective decision-making: Simple, Conventional, and Onerous. The Simple typology reflects participatory, trust-based, and consensus-driven strategic collective decision-making processes that are agile and responsive. The Conventional typology represents hierarchical and formalised governance, strategic collective decision-making processes that provide structure and predictability but may restrict adaptability. The Onerous typology captures strategic collective decision-making processes complicated by donor pressures, contested mandates, and interpersonal tensions, often resulting in protracted and fragmented outcomes. By situating these findings within established decision-making theories; encompassing rational, intuitive, and political perspectives, as well as the Cynefin framework; this study demonstrates how South African health NGOs navigate between order and complexity in their strategic collective decision-making processes. The analysis further integrates social capital and stakeholder perspectives to highlight how trust, networks, and external actors shape decision outcomes. The thesis advances the substantive theory of strategic collective decision-making as an interactive mode of organisational alignment, explaining how strategic leaders move fluidly between the three interconnected modes; Simple, Conventional, and Onerous; in response to contextual pressures, cultural norms, and organisational dynamics. This grounded typology provides new insights into how collective strategic decisions emerge through negotiation, relational trust, and compromise, rather than relying on linear or prescriptive logic. Beyond theoretical contribution, the study offers significant policy insights for strengthening governance and strategic collective decision-making in South Africa’s health NGO sector. It recommends embedding participatory and collective governance principles within the relevant governmental stakeholders, aligning accountability with inclusivity and relational engagement. Furthermore, the findings support shifts in national policy frameworks and health implementation frameworks toward collaborative governance that values cultural norms, relational capacity, and adaptive flexibility. By recognising health NGOs as strategic partners rather than implementers, this study contributes to building a responsive, community-centred, and resilient public health ecosystem in South Africa.
a grounded theory study
Keywords: Group decision making (http://id.loc.gov/authorities/subjects/sh85036201); Strategic planning (http://id.loc.gov/authorities/subjects/sh85128511); Grounded theory (http://id.loc.gov/authorities/subjects/sh90004682); Economic assistance (http://id.loc.gov/authorities/subjects/sh85040767); Non-governmental organizations (http://id.loc.gov/authorities/subjects/sh86007360); Management; Strategic alignment (https://www.wikidata.org/wiki/Q7621821)